THE ROLE OF NAILFOLD CAPILLAROSCOPY IN MONITORING LUNG INVOLVEMENT IN SYSTEMIC SCLEROSIS - Laura Groseanu; Patricia Paraschiva; Andra Balanescu; Violeta Bojinca; Daniela-Opris Belinski; Andreea Borangiu; Ioana Saulescu; Diana Mazilu; Sanziana Daia-Iliescu; Florian Berghea; Cosmin Constantinescu; Maria-Magdalena Negru; et al. (Romanian Journal of Rheumatology, 2019)
The usefulness of capillaroscopy in the follow-up of scleroderma patients and the possible prognostic role for the appearance of visceral involvement is suggested by many authors but still under debate.The aim of this study was to assess the role of monitoring capillaroscopic abnormalities (qualitative and semiquantitative) in relation with parameters of interstitial lung involvement and pulmonary arterial hypertension(PAH). A strong correlation was identified between initial capillaroscopy scores and FVC (r=-.47, p=0.002), DLCO (r=- .51, p< 0.001) and sPAP (r=0.34, p<0.001). Active and late capillaroscopic pattern were correlated with diagnosis of lung fibrosis (χ2=14, p=0.007) and PAH at follow-up examinations (χ2=14,2, p=0.007). Progression of capillaroscopic pattern at follow-up evaluations was not correlated with significant worsening of lung volumes, DLCO, sPAP. Instead, progression of microangiopathy evolution score (>1) was asociated with worsening of FVC (r=0.32,p<0.001), DLCO(r=0.21,p=0.02) and new diagnosis of lung fibrosis on HRCT (r=0,19,p=0.035). Semiquantitative scoring, rather then qualitative capillaroscopic assessment can have a predictive role for new involvement or worsening of previous lung involvement (especially interstitial lung disease) in scleroderma patients, confirming the putative role of capillaroscopy as biomarker in SSc.